Perancangan Sistem Stok Gudang Berbasis Website dengan Metode Waterfall - Cahyo Fajar Wibowo; Putri Aisyiyah Rakhma Devi (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2024)
Abstrak – Teknologi informasi saat ini berkembang semakin pesat terutama pada sektor industri, oleh sebab itu pada sektor industri memerlukan sebuah teknologi atau sistem informasi untuk mendukung proses bisnisnya agar lebih efektif dan efisien, namun pada PT Natuna Indah Permai (NIP) belum menggunakan sistem informasi pada proses bisnisnya, maka dari itu PT NIP mengalami sebuah permasalahan seperti: keterlambatan dalam pengecekan stok serta kesalahan dalam melakukan input data stok pada gudang, hal tersebut mengakibatkan terhambatnya pengadaan bahan baku dan juga proses produksi. Oleh sebab itu penelitian ini mengusulkan sistem untuk menghilangkan permasalahan pada PT NIP, penelitian ini membuat aplikasi stok gudang dengan fitur pencatatan data stok, dan pemantauan stok secara real-time, sehingga PT. NIP dapat mendata stok secara tepat dan cepat serta dapat membantu dalam manajemen pengadaan bahan baku untuk proses produksi.Kata kunci: waterfall, sistem informasi stok, uml, blackbox testing Abstract - Information technology is currently developing more and more rapidly, especially in the industrial sector. especially in the industrial sector, therefore the industrial sector needs a technology or information system to support its business processes to be more effective and efficient, but at PT Natuna Indah Permai (NIP) has not yet used more effective and efficient, but at PT Natuna Indah Permai (NIP) has not used information systems in its business processes, therefore PT NIP experiences an information system in its business processes. information system in its business processes, therefore PT NIP is experiencing a problem such as problems such as: delays in checking stock and errors in inputting stock data in the warehouse. inputting stock data in the warehouse, this resulted in hampering the procurement of raw materials and also the production process. Therefore This research proposes a system that can eliminate the problems This research makes a warehouse stock application with features of recording stock data, and real-time stock monitoring. stock data, and real-time stock monitoring, so that PT NIP can record stock appropriately and quickly and can help the procurement of raw materials and also production. NIP can record stock precisely and quickly and can assist in procurement management raw materials for the production process.Keywords: waterfall, stock information system, uml, blackbox testing